The Creation of Innovative Structure Model Affecting Commercial Bank Service Adoption in Thailand after Covid-19 Crisis - Srisornkompon, Palida (Journal of Applied Economics and Management Strategy, 2023)
The research on Structural Model Innovation that affects banking service utilization after the Covid-19 Crisis in Thailand aims to 1) restructure the bank according to the needs of consumers; 2) To study the bank structure that influences the decision to use the service, and 3) to study the bank structure that has the opportunity to predict the consumer decision to use banking services. A survey of 1,000 bank customers was conducted and the results were analyzed by logistic regression equation statistics. The study found that the main structural elements of the bank according to consumer needs consist of 5 structures: 1) offline customer service structure combined with marketing promotion 2) online customer service structure combined with marketing promotion 3) bank's ancillary service structure 4) structure of investment development in offline and online credit and 5) structure of the main operation. From the analysis of logistics regression equations, it was found that the 5 banking structures were: 1) offline customer service structure combined with marketing promotion 2) online customer service structure in conjunction with marketing promotion 3) bank's ancillary service structure 4) structure of investment development in offline and online credit and 5) structure of the main operation influencing the decision to use the banking service at the statistical significance level of 0.05. And the result of the prediction of the decision to use the service in descending order found that the structure of investment development in offline and online credit was predictable at 94.4 percent, followed by the structure of offline and online customer service combined with marketing promotion and core operation structure predicted 91.7 percent and the bank's ancillary service structure predicted 86.1 percent.